Description of Basic Knowledge Mathematics Students of Class X High Schools in Konawe District - Tina Suryawati; Nur Hasriani (Universitas Sembilanbelas November Kolaka, 2019)
This research is a type of exploratory research that aims to describe the Basic Mathematical Knowledge (PDM) of class X students of SMA Negeri in Konawe Regency. The population in this study were all grade X students of SMA Negeri in Konawe District, where the determination of the study sample was carried out by combining simple random sampling techniques (cluster random sampling) and proportion of strata (Proportional Stratified Random Sampling). The approach used is a quantitative approach, while the data analysis used is descriptive. Descriptive analysis is intended to describe the characteristics of research variables by using the highest score, lowest score, average, standard deviation, variance, and percentage of student achievement in each indicator. The average PDM test of students is still in the low category, with an average of 39.13. As many as 76.7% or 345 students from 450 samples scored below 50 with a standard deviation of 15.31. From 40 indicators of PDM questions tested, students were only able to answer four indicators well (presentation of correct answers above 70%).